PENERAPAN MODEL PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH SISWA KELAS X.2 DI SMAS TAMANSISWA TELUK BETUNG BANDAR LAMPUNG - Rafa, Nida Rasyidah; Ciciria, Deri; Febrianti, Aurora Nandia (Universitas Batanghari Jambi, 2025)
The aim of this research is to examine the improvement of students’ history learning outcomes through the application of the scramble learning model in class X.2 of SMAS Tamansiswa Teluk Betung, Bandar Lampung. This study employed classroom action research (CAR), carried out in two cycles, each consisting of four meetings with the stages of planning, implementation, observation, and reflection. The research was conducted collaboratively between the researcher and the history teacher. Data were collected using tests, observations, and documentation. The findings indicate that the use of the scramble learning model created an engaging and enjoyable learning atmosphere, which contributed to improved student achievement. In the pre-cycle, only 5 students achieved mastery with an average score of 60.68. In the first cycle, the number of students who met the mastery criteria increased to 15 students (51.72%). By the second cycle, the number rose significantly to 26 students (89.65%). In conclusion, the application of the scramble learning model effectively enhanced the history learning outcomes of class X.2 students at SMAS Tamansiswa Teluk Betung, Bandar Lampung.